Northern gene flow into southeastern East Asians inferred from genome-wide array genotyping - He, Guang-Lin (2022)
The population history of Southeast (SE) China remains poorly understood due to the sparse sampling of present-day populations and limited modeling with ancient genomic data. We report genome-wide genotyping data from 207 present-day Han Chinese and Hmong-Mien (HM)-speaking She people from Fujian and Taiwan Island, SE China. We coanalyzed 66 Early Neolithic to Iron Age ancient Fujian and Taiwan Island individuals obtained from previously published works to explore the genetic continuity and admixture based on patterns of genetic variations of the high-resolution time transect. We found the genetic differentiation between northern and southern East Asians was defined by a north–south East Asian genetic cline and our studied southern East Asians were clustered in the southern end of this cline. The southeastern coastal modern East Asians are genetically similar to other southern indigenous groups as well as geographically close to Neolithic-to-Iron Age populations, but they also shared excess alleles with post-Neolithic Yellow River ancients, which suggested a southward gene flow on the modern southern coastal gene pool. In addition, we identified one new HM genetic cline in East Asia with the coastal Fujian HM-speaking She localizing at the intersection between HM and Han clines. She people show stronger genetic affinity with southern East Asian indigenous populations, with the main ancestry deriving from groups related to southeastern ancient indigenous rice farmers. The southeastern Han Chinese could be modeled with the primary ancestry deriving from the group related to the Yellow River Basin millet farmers and the remaining from groups related to rice farmers, which was consistent with the northern China origin of modern southeastern Han Chinese and in line with the historically and archaeologically attested southward migrations of Han people and their ancestors. Our estimated north–south admixture time ranges based on the decay of the linkage disequilibrium spanned from the Bronze Age to historic periods, suggesting the recent large-scale population migrations and subsequent admixture participated in the formation of modern Han in SE Asia.